1997
DOI: 10.1007/s004240050466
|View full text |Cite
|
Sign up to set email alerts
|

Low- and high-blood flow regions in the normal pig heart are equally vulnerable to ischaemia during partial coronary stenosis

Abstract: Myocardial perfusion is heterogeneous, even in the normal heart. It is unknown whether the resting normal blood flow level predicts the severity of mismatch between local blood flow and metabolism during acute ischaemia. In the present study local blood flow (measured with radioactively labelled microspheres) and metabolic indicators of ischaemia [tissue contents of lactate and inosine (INO), a breakdown product of adenosine triphosphate (ATP)] were determined in 84-102 simultaneously frozen samples (approxima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 29 publications
0
12
1
Order By: Relevance
“…The considerable spatial heterogeneity of energy turnover demonstrated in the present study may also explain the recent finding that during low-flow ischemia there is no uniform flow threshold for biochemical markers of ischemia (adenosine, inosine, lactate) to rise [3,20]. In contrast, only when the individual local flow decreased by approximately 50% did adenosine and lactate increase.…”
Section: Spatial Heterogeneity Of Energy Metabolismcontrasting
confidence: 44%
“…The considerable spatial heterogeneity of energy turnover demonstrated in the present study may also explain the recent finding that during low-flow ischemia there is no uniform flow threshold for biochemical markers of ischemia (adenosine, inosine, lactate) to rise [3,20]. In contrast, only when the individual local flow decreased by approximately 50% did adenosine and lactate increase.…”
Section: Spatial Heterogeneity Of Energy Metabolismcontrasting
confidence: 44%
“…Low-flow areas had lower V O 2 and highflow areas had higher V O 2 . Further studies showed that areas of the left ventricle that receive a relatively low amount of blood flow are not in a hypoxic state, suggesting local adaptation of blood flow to oxygen demand (8,11,14). However, direct measurement of aerobic metabolic flux in small myocardial regions became possible only recently.…”
mentioning
confidence: 99%
“…Previous studies showed that regions of high blood flow and metabolic demand, as determined under basal conditions without coronary constriction, are metabolically stressed to a similar extent during hypoperfusion as regions with a low basal blood flow (9,27). Tissue damage following severe ischemia is more frequent in regions with high blood flow under normal conditions (19), which may be related to the higher metabolic rate in these regions.…”
Section: Discussionmentioning
confidence: 97%
“…The vulnerability of low-vs. high-control blood flow regions has been investigated previously (9,19,27). Here, we plotted oxygen extraction against basal blood flow at t ϭ 0 (Fig.…”
Section: Mdo2mentioning
confidence: 99%
See 1 more Smart Citation